Synthesis and Biological Activities of Aspirin-Azo Derivatives - Ho, Boon Kui (Universiti Malaysia Sarawak (UNIMAS), 2017)
The chemistry of aspirin and azo derivatives has been widely studied for pharmaceutical purposes. In this study, a series of halogenated azo derivatives 47-49(a-d) and aspirinhalogenated azo derivatives 50-52(a-d) were successfully synthesised. Halogenated azo derivatives 47-49(a-d) were synthesized via coupling reaction while aspirin-halogenated azo derivatives 50-52(a-d) were synthesised via esterification reaction of aspirin with 47- 49(a-d). The structures of all the synthesized compounds were characterized by using elemental analysis (CHNS), nuclear magnetic resonance (1H NMR and 13C NMR) and Fourier Transform infrared (FTIR) spectroscopies. All compounds were evaluated for antibacterial activities against Escherichia coli ATCC 25922 and Staphylococcus aureus S48/81 via turbidimetric kinetic method. Compounds 47-49(a-d) showed good antibacterial activity against E. coli and S. aureus due to the presence of halogen substituents and -N=N- groups, which played significant role in antibacterial activities. The synthesised aspirin–halogenated azo derivatives 50-52(a-d) showed weak antibacterial activity against tested bacteria due to bulky molecular structure thus hindered the penetration into bacterial cell wall. All compounds were also further screened for their anticancer activities against nasopharyngeal cancer cell lines HK-1 using MTS [3-(4,5- dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide]-based colorimetric assay. Among 47-49(a-d), compound 47a and 49a showed good cell inhibition against HK-1. Aspirin–halogenated azo derivatives 50-52(a-d), on the other hand, exhibited weak cancer cells inhibition due to possible weak binding into EGFR tyrosine kinase.